2017
DOI: 10.1007/s10531-017-1307-y
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian decline, pond loss and reduced population connectivity under agricultural intensification over a 38 year period

Abstract: Habitat loss, together with less obvious land-use changes such as intensified farming practice, can have significant adverse impacts on biodiversity. An important factor in determining the ability of species to cope with such changes is their potential to sustain a populations network by dispersal across the landscape. Habitat quality and structure are particularly important for surface-dwelling species with low dispersal abilities, such as amphibians. To assess this ecological function, ponds in a coastal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 78 publications
3
67
1
Order By: Relevance
“…, Ferreira and Beja , Arntzen et al. ). In many cases, the remaining aquatic habitats became less favorable for the establishment of native aquatic fauna (Ficetola et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Ferreira and Beja , Arntzen et al. ). In many cases, the remaining aquatic habitats became less favorable for the establishment of native aquatic fauna (Ficetola et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Arntzen et al. ), and paedomorphic newts have suffered particularly dramatic population losses (Denoël et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Amphibians are one of the most at‐risk groups of taxa in agricultural areas (Cushman, ; Arntzen et al ., ) due to their complex life‐history and narrow habitat tolerances, which can make them susceptible to rapid changes in habitat and microclimate (Cushman, ; Barrett & Guyer, ; Cogger, ). Consequently, many amphibians are threatened with extinction worldwide, more so, than any other vertebrata (Wake & Vredenburg, ; Thompson et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…, Arntzen et al. ), yet few studies are large enough in sample size and time frame to adequately address climate (using weather‐related covariates as representatives of climate). In addition, sampling amphibians is difficult and sampling variation is often a high proportion of total variation in demographic estimates used to identify trends, thus further confounding our ability to identify declining populations with confidence (Pechmann and Wilbur , Shaffer et al.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying population declines is challenging in amphibians because most populations are characterized by large fluctuations in abundance in response to changes in environmental conditions (high process variation; Alford and Richards 1999). Despite the difficulty, previous studies have identified various environmental factors, including weather and climate, as contributors to decline (Daszak et al 2005, Arntzen et al 2017), yet few studies are large enough in sample size and time frame to adequately address climate (using weather-related covariates as representatives of climate). In addition, sampling amphibians is difficult and sampling variation is often a high proportion of total variation in demographic estimates used to identify trends, thus further confounding our ability to identify declining populations with confidence (Pechmann and Wilbur 1994, Shaffer et al 1998, Whiteman and Wissinger 2005.…”
Section: Introductionmentioning
confidence: 99%